Rebound serum bilirubin levels after single vs. double phototherapy - Widyastuti Widyastuti; Supriatmo Supriatmo; Guslihan Dasa Tjipta (Paediatrica Indonesiana, 2014)
Background Hyperbilirubinemia is the most common clinicalphenomenon found in newborns. Phototherapy is the standardtreatment for lowering bilirubin levels in neonates. Whileintensive (double) phototherapy produces a more rapid declinein serum bilirubin levels than standard (single) phototherapy,greater rebound effects may occur.Objective To assess bilirubin levels in neonates with hyperbilirubinemiawho underwent single or double phototherapy, includingrebound bilirubin levels after phototherapy termination.Methods An open, randomized, controlled trial was con ductedat H. Adam Malik Hospital and Dr. Pirngadi Hospital, Medan,from August 2009 until January 2010. Subjects with indirecthyperbilirubinemia were divided into two groups. One groupreceived single phototherapy (n = 41) and other receiveddouble photo therapy (n = 40) . Measurements of total plasmabilirubin level were conducted at 12 hours and at 24 hoursof phototherapy, as well as at 24 hours after phot otherapytermination. Rebound bilirubin serum level was defined asan increment of about 1 - 2 mg/dL serum bilirubin afterphototherapy discontinuation.Results The decreases in serum bilirubin levels were significantlygreater in the do uble phototherapy group for observationsat 12 h ours , 24 h ours, and 24 hours after phototherapyt ermination (P = 0.0001). At the 24-hour observation afterterminationofphototherapy, only 1 neonate (2.7%) in the singlephototherapy group compared to 4 neonates (10.8%) in thedouble phototherapy group had serum bilirubin level increasesof 1 - 2 mg/dL. Fisher's exact test did not reveal a significantdifference in rebound serum bilirubin occurrence in the twogroups (P = 0.358).Conclusion Double phototherapy shows significantly greaterdecrease in bilirubin level compared to single phototherapywithin a same period of time. Rebound serum bilirubin levels aftersingle and double phototherapy may occur in some patients withhyperbilirubinemia, as bilirubin production continues. However,260 • Paediatr Irulones, Vol. 54, No. 5, September 2014there is no significant difference in rebound effects between singlevs. double phototherapy.